Regulation of immunogenic cell death and potential applications in cancer therapy - Fang, Kun; Yuan, Shuai; Zhang, Xue; Zhang, Jingdong; Sun, Shu-lan; Li, Xiaoxi (Frontiers in Immunology, 2025)
Immunogenic cell death (ICD), a type of regulatory cell death, plays an important role in activating the adaptive immune response. Activation of the tumor-specific immune response is accompanied by the cell surface exposure of calreticulin and heat-shock proteins, the secretion of adenosine triphosphate, and the release of high mobility group box-1. In this review, we summarize and classify the latest types of ICD inducers and their molecular mechanisms, and discuss the effects and potential applications of inducing ICD by chemotherapy drugs, targeted drugs, and oncolytic viruses in clinical research. We also explore the potential role of epigenetic modifiers in the induction of ICD, and clarify the synergistic anti-tumor effects of nano-pulse stimulation, radiosensitizers for radiotherapy, photosensitizers for photodynamic therapy, photothermal therapy, and other physical stimulation, combined with radiotherapy and chemotherapy induced-ICD, in multimodal immunotherapy. In addition, we elucidate the molecular mechanism of ICD in detail, including the calcium imbalance, mitochondrial stress, and the interactions in the tumor microenvironment. Ultimately, this review aims to offer deeper insight into the factors and mechanisms of ICD induction and provide a theoretical basis for the future development of ICD-based immunotherapy.